Codis str loci (csf1po, thoi, tpox, vwa) genetic variation analysis in madurese - Yudianto, Ahmad; Sosiawan, Agung; Margaret, Nola (Folia Medica Indonesiana, 2017)
Endogamy continues to occur among the Madurese people in rural areas of the island of Madura, especially those areas of the smallest islands around the mainland of Madura. Endogamy as seen from a genetic standpoint will increase the frequency of homozygote genotypes. With regard to genetic variations, STRs of nuclear DNA and polymorphisms in mtDNA are frequently examined. Genetic variations in human undergo an evolutionary process through the accumulation of changes in DNA sequence, i.e. through the process of nucleotide substitutions that evolves in number with the directional development of lineage. So far, the genetic variations among the populations in Madura Island have not been known. The present study was an observational analytical research with the purpose of determining the genetic variations in STR CODIS in the populations of Madura Island. Results indicated that, based on loci alelle: CSF1PO, THOI, TPOX, and vWA, there was homozygote genotypes. The allele variations is not specific for Madurese ethnic but this variations may represent married model in Madurese ethnic. According to Mustama (2007), a gene pool is not only a collection of genes but a dynamic system organized and containing the past history of a population. Any genetic information has certain historical, anthropological and statistical aspects necessitating an interdisciplinary coordination and collaboration.